Analisis Pengelolaan Aset Desa Terhadap PAD Desa: (Studi Kasus Desa Wolokisa Kecamatan Mauponggo) - Ermelinda Saputri Weni; Sayful Amrin (Program Studi Pendidikan Ekonomi FKIP Universitas Flores, 2025)
The purpose of the research in Wolokisa Village, to find out; (1) how thegovernment manages village assets, and (2) the efforts of the village government in increasingthe original income of the village. The type of research is qualitative. Data collection usesobservation, interview and documentation techniques. The collected data are then analyzedusing Milles and Huberman Interactive analysis. The results of the study show that the processof planning, procurement, administration, reporting and supervision of village assets in thevillage (1) the success of village asset management is influenced by the participation of thevillage community, and the demands as village heads and village officials, namely masteringor knowing what the main needs are in the village. In my opinion, in Wolokisa Village thereare still difficulties in terms of infrastructure such as roads as access to the community's economy and the lack of community knowledge in the use of village assets. (2) limitedregulations, this condition makes it difficult and delays for the village government in masteringvillage activity and financial planning. Human Resources (HR) of the community are stillminimal and only expect donations from the government and other parties